Beginning at the End: The Kingdom of God in 1 Corinthians - Carr, David (The catholic biblical quarterly, 2019)
This essay examines Paul's references to the kingdom of God in 1 Corinthians. In doing so, it takes a decidedly particular, yet fundamental and necessary, step in the direction of constructing a Pauline theology of the kingdom of God. Instead of following traditional paths to explicate Paul's understanding of God's kingdom by comparing Paul's references with Jesus's kingdom proclamation, constructing a Pauline view from passages that span the Pauline corpus, or focusing exclusively on the kingdom's temporal dimensions, I restrict my study to ἡ βασιλεία in the literary context of 1 Corinthians. By identifying three dimensions of God's kingdom in the epistle - existential, moral, and social - I argue that Paul presents the kingdom of God as Christ's empowerment of the Corinthians' present existence, as well as his governance of their moral and social relationships over and against competing powers.